2019
DOI: 10.1088/1612-202x/ab3451
|View full text |Cite
|
Sign up to set email alerts
|

Improving the 13CO2 content measurement accuracy in exhaled air using the Kalman technique for filtering the experimental signal obtained by the tunable diode laser absorption spectroscopy method with the frequency modulation of the diode laser pump current

Abstract: This paper reports on the application of the Kalman method for processing the signal obtained by the tunable diode laser absorption spectroscopy method in an experimental circuit, which includes the frequency modulation of a diode laser pump current in combination with the synchronous detection technique. It has established that the implementing of this approach makes it possible to improve the measurement accuracy of the 13 CO 2 content, as well as the measurement accuracy of the 13 CO 2 and 12 CO 2 concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Earlier, this method was used to measure the content of 13 C 16 O 2 (636) in a mixture with 12 C 16 O 2 (626) in exhaled air. Performed studies have shown that one of the most promising ranges for measurements is the region near a wavelength of 2 µm (frequency range: 4860-4880 sm −1 ), which contains a number of absorption curves of these molecules, to a minimum extent overlapping, and the experimental arrangement does not require complex and expensive equipment [18][19][20]. To accurately measure the content of 13 C 16 O 2 and 12 C 16 O 2 in the analyzed mixture, knowledge of the absorption constantvalues and their pressure dependence, since the measurements can be carried out at different pressures, are necessary.…”
Section: Figure 1bmentioning
confidence: 99%
“…Earlier, this method was used to measure the content of 13 C 16 O 2 (636) in a mixture with 12 C 16 O 2 (626) in exhaled air. Performed studies have shown that one of the most promising ranges for measurements is the region near a wavelength of 2 µm (frequency range: 4860-4880 sm −1 ), which contains a number of absorption curves of these molecules, to a minimum extent overlapping, and the experimental arrangement does not require complex and expensive equipment [18][19][20]. To accurately measure the content of 13 C 16 O 2 and 12 C 16 O 2 in the analyzed mixture, knowledge of the absorption constantvalues and their pressure dependence, since the measurements can be carried out at different pressures, are necessary.…”
Section: Figure 1bmentioning
confidence: 99%
“…One of the most promising, among the various methods for 13 C 16 O 2 detection, is the tunable diode laser absorption spectroscopy (TDLAS) method using singlefrequency tunable diodes lasers (TDL) as radiation sources [12][13][14][15][16][17][18][19][20]. Spectroscopic constants such as positions of the vibrational-rotational absorption lines centres, their intensities, the dependence of absorption constants and cross-sections on pressure, collision broadening constants, etc, are measured with great accuracy using this method.…”
Section: Introductionmentioning
confidence: 99%